Risk factors for puerperal anemia in immediate postpartum women at a high-altitude hospital - Apaza-Justo, Brigitt (2026)
Introduction: Puerperal anemia is a public health problem with high prevalence in developing countries. In Peru, it is estimated to affect up to 50% of women in the immediate postpartum period, with regional variations. In Puno (3827 m.a.s.l.),, the department where Carlos Monge Medrano Hospital is located, altitude and socioeconomic conditions may contribute to a higher prevalence. However, no recent studies have assessed its magnitude and risk factors in this area. Objective: To evaluate the risk factors associated with puerperal anemia in immediate postpartum women. Methods: Observational, cross-sectional, and correlational study. A total of 200 immediate postpartum women attended at the hospital in 2023 were analyzed. Data were collected using a structured data collection form and analyzed with Chi-square tests and Poisson regression. Results: The prevalence of puerperal anemia was 79%. Postpartum hemorrhage increased the risk of anemia by 128% (cPR: 1,288; aPR: 1,264), while rural origin increased the risk by 119% (cPR: 1,196; aPR: 1,166). Additionally, 41,3% of the postpartum women had moderate anemia, 37,7% had mild anemia, and 21% had severe anemia. Women with a history of gestational anemia had a significantly higher risk of developing puerperal anemia (cPR: 1,432; aPR: 1,398). Conclusions: Puerperal anemia has a high prevalence in the studied population and is associated with postpartum hemorrhage, rural origin, and a history of gestational anemia.